The Effects of Emotional Intelligence on Interpersonal Facilitation of Managers and Supervisors: Empirical findings from Public Sector Enterprises in Kerala - Jils Baby Emmanuel and Santhosh. P. Thampi
Research and discussions of EI predicted the possibility of the linkage between Emotional Intelligence skills and interpersonal facilitation. This study was conducted to examine empirically the extent to which Emotional Intelligence contributes to the interpersonal behaviours of managers and supervisors in Public Sector Enterprises in Kerala. The sample comprised of 500 respondents of which 243 were Managers and 257 were Supervisors in Public Sector Enterprises in Kerala. The data were analysed using SPSS 21 in which tools such as ANOVA, Correlation and Regression were applied. The results indicated that there is highly significant and positive relationship between Emotional Intelligence and interpersonal facilitation of managers and supervisors of Public Sector Enterprises in Kerala.